Implementation of Experiential Learning-Based Edupreneurship through Student Cooperatives to Cultivate the ‘Santripreneur’ Spirit in Islamic Boarding Schools - Arly Zahra Maulida; Qonita Rahmawati; Amiirotul Majidah; Cecep Sobar Rochmat (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Developments in the world of education require Islamic boarding schools (pesantren) not only to produce graduates who excel in religious studies but also to provide opportunities for developing entrepreneurial competencies aligned with Islamic values. This study aims to analyze the implementation of experiential learning-based edupreneurship through the Student Cooperative (Kopel) division of the Pondok Modern Student Organization (OPPM) and to describe the development of the “santripreneur” spirit at Modern Islamic Boarding School Darussalam Gontor for Girls 1st Campus. This study employed a descriptive qualitative approach. Data were collected through participatory observation, in-depth interviews with three informants consisting of Kopel mentors/advisors and Kopel administrators, and documentation of cooperative activities and administrative records. Data were analyzed using the Miles and Huberman interactive model through data condensation, data display, and conclusion drawing and verification. Data credibility was established through source and technique triangulation. The findings indicate that edupreneurship through Kopel is implemented through planning, management, service, and evaluation activities that directly involve students in cooperative operations. These activities provide students with experiential learning opportunities in leadership, responsibility, decision-making, problem-solving, financial management, teamwork, and service. The findings also show that students’ involvement in cooperative activities is associated with the development of santripreneur characteristics, including independence, discipline, responsibility, creativity, collaboration, and integrity, which are practiced within the framework of Islamic values. Thus, Kopel functions not only as a business unit but also as a practical learning environment for developing entrepreneurial competencies and Islamic character among students.